English language teaching textbook evaluation of curriculum 2013: Teachers’ perspectives - Harni Jusuf (English Education Department, 2022)
There are four interrelated aspects in teaching learning process that is teacher, students, materials, and evaluation and assessment. The things that should be paid attention related to materials are materials selection, materials development and design, and materials evaluation or textbook evaluation. Regarding to textbook evaluation, this article aims to investigate teachers’ perspectives on textbook of curriculum 2013 or K 13 for the second grade. Eighteen teachers both from public and private vocational high schools in Gorontalo city were asked to assign their opinions about the textbook of K 13 using checklist method adapted from Al Harbi. The five categories of Al Harbi in questionnaire are: layout and design, the objectives of the textbook, teaching methods and activities, language skills, and evaluation. The data from checklist were entered into excel program to find out the percentage, mean, and standard deviation. Afterward, the findings of excel analyzed descriptively. The study’s result revealed that the averages mean score of layout and design was 4.01, the objectives of the textbook was 4.18, teaching methods and activities was 3.84, language skills was 3.99, and evaluation was 3.89. Therefore, from the perspectives of English teachers, they agree that the English textbook for the second grade of vocational high school is appropriate to be used.